Financial Constraints of Micro, Small, and Medium-sized Enterprises (MSMEs) in the Indonesia Creative Industries - Ninditya Nareswari; Nuraini Desty Nurmasari; Latifah Putranti (Journal of Economics, Business, and Accountancy Ventura, 2022)
The creative industry has a significant role in the economy. The existence of a creative industry causes advanced innovations, increases job availability, and improves the value and quality of a product. However, MSMEs in the creative industry still face constraints related to finance because they have different types of business patterns. The business pattern is unpredictable and will have an impact on strategy. This study aims to identify and explore the financial constraints of MSMEs in the creative industry in Surabaya. A semi-structured interview was conducted with the owner of 8 MSMEs. Using an explanatory pilot study, the result found five themes of the financial constraints of MSMEs in the creative industry: working capital management, access to credit, financial support from the government, cost efficiency, and the financial literacy of the owners. This study has several implications for the creative economy to develop the financial aspect for MSMEs in the creative industry.